Insider Trading: Isu Etika, Peraturan dan Sudut Pandang Trader - Arief Zuliyanto Susilo (Journal of Accounting and Investment, 2014)
Basically all humans are ethical. When a person experiences an inner conflict in the act is less precise, it is a sign that the person has ethics. Basically also that every person, especially the economic actors are individuals who have opportunistic nature. Options for increasing the personal wealth without thinking of the other party, as long as does not violate or potentially against the law, will be performed. Act of buying and selling by the parties in a debate that still has not led. The researchers have delivered a variety of rationale. Insider trading like a double-edged sword, on the one hand can be stretched buying and selling stocks, on the other hand have an impact on the loss for the other party. Various attempts have been made to remove the various agencies insider trading activities, but insider trading is an activity that is sometimes very difficult to detect and impossible someone dibatas right to sell his possessions. By using literature review and interviews with traders, it was concluded that insider trading will occur if the beneficial regardless of ethical problems. There needs analysis and proper consideration in determining the classification cutoff ethical or not insider trading or selling the permissible limits.